Pendampingan Menulis Buku Antologi untuk Meningkatkan Literasi Siswa - Yusuf, M.; Hafidz Miftahuddin, Abdul; Arofik, Slamet; Maryam Qurotul Aini, Siti (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2024)
This study aims to describe the mentoring of writing an anthology as an effort to improve students' literacy in the Muadalah Education Unit (SPM) of Madrasah Ulya PP. Miftahul Mubtadiin Nganjuk. The study actively involves students in the entire process of mentoring writing an anthology. The background of the study includes literacy issues faced by students in the SPM environment and the importance of mentoring writing an anthology in addressing these challenges. The mentoring method used is the Participatory Action Research (PAR) approach, which involves students in identifying topics, collecting and sharing experiences, and participating in the editing and publishing process of the anthology book. Through this active participation, students can develop their writing skills, enhance their reading interests, and strengthen their literacy. The results of the mentoring show a significant improvement in students' literacy after participating in the mentoring of writing an anthology book. Students not only develop their writing skills but also enhance their understanding of the importance of literacy in daily life. They also experience satisfaction in contributing their voices through the writings immortalized in the anthology book. This research provides a significant contribution to the development of students' literacy in the SPM of Madrasah Ulya PP. Miftahul Mubtadiin Nganjuk through mentoring writing an anthology book. This article also offers practical implications for educators and researchers in adopting this method to enhance students' literacy in other educational institutions.